Theoretical Research on the Movement Law of Water Cone Behavior in Heavy Oil Reservoirs with Bottom Water. (17th June 2022) - Wang, Kai; Tang, Chenyang; Zhang, Tianyou; Gao, Yufei; Zou, Jingyun; Jiang, Yan; Sun, Kuo; Chen, Yan
Abstract : Aiming at the unclear reorganization of a water cone shape, its sweep range, and water saturation distribution of horizontal well in heavy oil reservoirs with bottom water, a mathematical method was proposed in this paper to establish a microtube model and physical model with the starting pressure gradient (SPG) to study the water cone behavior. The results showed that the different water-cut stage, mobility, depth from oil-water interface (DOWI), and liquid production strength have an obvious impact on water cone behavior. Moreover, we found an interesting phenomenon on an extreme point in water saturation derivation among water cone, which could be a reason for further adjustment. Finally, we confirmed the calculation results with physical simulation, which is highly consistent. The new method proposed in this paper was significant in the water cone behavior study and has a broad application in heavy oil reservoir development in the future.